ANALYSIS ON THE EFFECT OF OIL PRICE, DOLLAR EXCHANGE RATE, AND STOCK EXCHANGE INDEX ON GOLD PRICE IN USA DURING 2006-2012 - Revo Rosheno Arbes; Arif Hoetoro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
By using time series data from January 2006 up to December 2012, this research aims at finding the dimensional influence of oil price, U.S. Dollar exchange rate and stock exchange index on gold price. For examining the influence of the independent variables toward the dependent variable, Error Correction Model (ECM) is used along with t-test and F-test to reveal the relation and the influence of the pre-determined variables.The findings show that, in short-run, U.S Dollar exchange rate and stock exchange index have significant effect on gold price. U.S Dollar exchange rate has positive and significant effect on gold price, while stock exchange index has inverse and significant effect on gold price. Meanwhile, Oil Pricet-1, USD exchange ratet-1, and Stock exchange indext-1 are not significant and do not affect gold price in long run. The most influential variable to gold price is U.S. Dollar exchange rate which strongly affect gold price in short-run and stock exchange indext-1 which likely affect gold price in long-run. Keywords: Gold Price, Oil Price, Dollar Exchange Rate, Stock Exchange Index